Haktywizm i inne formy aktywizmu internetowego jako nowe mechanizmy demokracji bezpośredniej - Janik, Jagoda (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2016)
The point of my eassay is to show how traditional mechanisms of direct democracy are nowadays accompanied by new ways in which citizens state their postulates and also effectively influence or even change political decissions. In the first part of my essay I would like to point out some crucial changes in the way society is comunicating today with public power. I would like to emphasize the role of the new technologies in the political process, mainly in proposing the new ideas to the public power, as well as commenting on the recent projects or drafts. The technology also changed the way of keeping contact between citizens and government. This change is the most relevant when it comes to direct democracy, as the traditional forms of it may turn out to be unsufficient in many cases. In the further part of my essay I would like to concentrate on specific types of activism that can be taken by individuals via internet. The most widely known example of such types is hacktivism, pursuaded by people with bigger and more advanced knowledge of technology. Yet, some of the particular actions taken by such groups, in particular by Anonymous, have managed to have bigger impact and been joined by people not related to the group. Also as a conclusion I would like to point out even newer forms of internet activism, which can be taken by ordinary citizens.
Keywords: Anonymous; hacktivism; Chanology; ACTA; teledemocracy; infoactivism; internet